(untitled) (Nexo Revista Científica, 2021)
The main aim of the article is to review modern concepts of the legal principle of rational nature management. To fulfil that aim, a descriptive-analytical and data-gathering methods are utilized. The principle of rational environmental management should be considered as a modern paradigm of environmental and legal regulation. The article substantiates that this paradigm includes doctrinal views on the legal support of rational use of natural resources, state environmental policy, a set of existing legal norms on rational use of natural resources, legal relations on the use of natural resources, and a developed ecological culture. The authors concluded that the central core and an obvious trend in the environmental management paradigm is the idea of the best available technologies.